2021
DOI: 10.1088/1361-6579/ac023b
|View full text |Cite
|
Sign up to set email alerts
|

Development of an electrical impedance tomography set-up for the quantification of mineralization in biopolymer scaffolds

Abstract: Objective. 3D cell cultures are becoming a fundamental resource for in-vitro studies, as they mimic more closely in-vivo behavior. The analysis of these constructs, however, generally rely on destructive techniques, that prevent the monitoring over time of the same construct, thus increasing the results variability and the resources needed for each experiment. Approach. In this work, we focus on mineralization, a crucial process during maturation of artificial bone models, and propose electrical impedance tomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Based on these results the custom-made spectrometer device appears as a useful option to perform real-time/in-line analysis of TEed constructs. Its cost and performance make it competitive with other recently proposed non-destructive approaches [26]. Furthermore, the small dimensions allow us to consider the device as a component that can be easily integrated on board of recently prototyped bioreactor systems [27][28][29][30][31], for the monitoring of the TEed constructs during their conditioning.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results the custom-made spectrometer device appears as a useful option to perform real-time/in-line analysis of TEed constructs. Its cost and performance make it competitive with other recently proposed non-destructive approaches [26]. Furthermore, the small dimensions allow us to consider the device as a component that can be easily integrated on board of recently prototyped bioreactor systems [27][28][29][30][31], for the monitoring of the TEed constructs during their conditioning.…”
Section: Discussionmentioning
confidence: 99%
“…As detailed in the previous sections, these methods are largely connected with cell destructive processing. While the alternative approaches already described maintain their general validity, other methods specific for the evaluation of changes in matrix properties have been proposed for the study of artificial bone substitutes ( Cortesi et al, 2021b ; Lovecchio et al, 2022 ; Arunngam et al, 2018 ). They are based on either EIT or spectroscopic techniques and aim at quantifying different calcium-based components that are typical of cell-induced mineralization.…”
Section: Matrix Interactionmentioning
confidence: 99%
“…Our works on the topic ( Cortesi et al, 2021b ; Lovecchio et al, 2022 ) rely on a different experimental model that grants better reproducibility and a higher level of control. Indeed, the amount of minerals produced by the cells is highly dependent on the type of cells and the experimental protocol employed.…”
Section: Matrix Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, You et al first reported the case of retroperitoneal hemorrhage EIT monitoring in patients with renal trauma ( You et al, 2013 ), and Liu et al reported the first study on non-invasive monitoring of cerebral blood volume during total aortic arch replacement ( Liu et al, 2019 ). In addition to the abovementioned fields, EIT has extensive applications in biomedical areas, such as cell culture monitoring ( Yang et al, 2019 ; Schwarz et al, 2020 ; Liu et al, 2022b ) and bioimpedance analysis ( Cortesi et al, 2021 ). These studies fully demonstrate that EIT, as a new medical imaging technology, is gradually becoming a powerful supplement to traditional medical imaging technology.…”
Section: Introductionmentioning
confidence: 99%